Sand-Dust Storm Simulation Model Coupled with PSU/NCAR Mesoscale Model - J.R. Jiang; X.Y. Zhang; C.H. Zhou; H.L. Liu; X.B. Chi (Journal of Algorithms & Computational Technology, 2013)
A sand-dust numerical model coupled with MM5(PSU/NCAR mesoscale model) –CUCSDust (CMA Unified Chemistry System-Dust) is introduced. CUCSDust includes such detail physical processes as dust production, transport, growth, coagulation, dry and wet deposition, which can simulate and forecast the initial and sand-dust concentration of sand and dust storm. A parallel scheme is also designed to reduce the run-time which is most important for real-time forecasting. Based on CUCSDust, a numerical model forecasting system is established in northeast Asia, and is applied to China Meteorological Administration (CMA) for operational prediction of sand and dust storm from March, 2006. A prediction result of severe sand and dust storm occurred in 26–28, March, 2006 is chosen, which shows no difference for sand-dust spatial distribution between model outputs and remote sensing monitoring imagers and indicates that the model system has the capability of real-time forecasting sand and dust storm in northeast Asia.*